A novel and efficient ammonia leaching method for recycling waste lithium ion batteries. (1st April 2020) - Qi, Yaping; Meng, Fansong; Yi, Xiaoxia; Shu, Jiancheng; Chen, Mengjun; Sun, Zhi; Sun, Shuhui; Xiu, Fu-Rong
Abstract: Effective recycling waste lithium-ion batteries (LIBs) are of great economic and environmental benefits. This study proposes a novel and efficient ammonia leaching method for recovering Co and Li from waste LIBs. This method yields a Co and Li leaching rate of 91.16% and 97.57%, respectively, under the optimal conditions (NH3 ·H2 O 120 g/L, NH4 HCO3 75 g/L, n (Na2 SO3 ): n (Co) = 2:1, 353 K, 240 min). Leaching kinetics also show that the speed-limiting step in this process is the interfacial chemical reaction, and the activation energy of Co and Li is 58.45 kJ mol −1 and 50.05 kJ mol −1, respectively. Moreover, scanning electron microscopy (SEM), energy dispersion spectrum (EDS), and x-ray diffraction (XRD) results indicate that the morphology of waste LIB powder are irregular granular and lamellar. Under the optimal condition, however, the leaching residues are scattered particles at a smaller size and the as formed MnCO3 particles are smooth with a uniform cubic structure. Besides, MnCO3 and graphite in the leaching residues can be separated and recovered. After that MnCO3 was further calcined to Mn3 O4, a precursor for the production of new LIBs. Hence, a new and effective way for spent LIBs circular recycling is put forward, providing another choice for spent LIBs recycling industry. Graphical abstract: Image 1